"I Wanted to Rebel, But There They Hit Me Even Harder": Discourse Analysis of Israeli Women Offenders' Accounts of Their Pathways to Substance Abuse and Crime. (May 2016) - Gueta, Keren; Chen, Gila
This study examined women offenders' accounts of their pathways to substance abuse and crime and the intersection between them, to reach a holistic understanding that captures the dynamics of victimization, agency, and gender. Discourse analyses of the accounts of 11 Israeli women offenders indicated differential use of two discourses. Five participants used the victimization discourse, which viewed substance abuse as an attempt to medicate the self that was injured following victimization experiences; two used the agency discourse, which viewed substance abuse as a way to experience pleasure, leisure, and control over their destiny. Four of the participants used these two contradictory discourses simultaneously. The findings indicate the absence of a cultural discourse that encompasses women's complex experience of gender, victimization, and agency. Possible implications for intervention are discussed.